Resistance to artemisinin of malaria parasites (Plasmodium falciparum) infecting α-thalassemic erythrocytes in vitro. Competition in drug accumulation with uninfected erythrocytes - S. Kamchonwongpaisan (2018)
Plasmodium falciparum infecting hemoglobin (Hb)H and/or Hb Constant Spring erythrocytes has higher resistance to artemisinin in vitro than when infecting normal erythrocytes. This is due to low drug accumulation of infected erythrocytes resulting from competition with uninfected variant erythrocytes, which have a higher accumulation capacity than genetically normal cells. Drug accumulation of the parasite was shown to be saturable and dependent on metabolic energy. The 50% inhibitory concentrations (IC 50 's) for the parasite in HbH/Hb Constant Spring erythrocytes were decreased when normal erythrocytes were added to the infected cells, and correspondingly, the IC 50 's in normal erythrocytes were increased when HbH/Hb Constant Spring erythrocytes were added to the infected cells. The changes of IC 50 corresponded to the variation in drug accumulation of mixtures of normal and variant erythrocytes of different compositions. The IC 50 's for the parasite in variant erythrocytes were also greatly decreased when the hematocrit of the culture was lowered, while the IC 50 's in normal erythrocytes were independent of the hematocrit. The increase in IC 50 values for the parasites infecting variant erythrocytes was also related to the decrease in parasite accumulation, indicating that drug accumulation capacity of the parasite also has a role in determining drug sensitivity. Artemisinin sensitivity therefore is determined by its accessibility to the parasite, which is decreased in infected variant erythrocytes.